Hybrid Power Generation Model using Wind Energy and Solar Energy - Mukherjee, Soumya; Jana, Sougata; Roy, Amartya; Santra, Swapan (International Journal of Computer Sciences and Engineering, 2025)
One of the basic needs for development of any nation in the world is to provide reliable and steady supply of electricity. Now-a-days the electrical energy is considered to be the driving force for social and economic development of a nation. To cope with the growing demand of electricity, it is become a necessity to generate power from different renewable energy resources. In context of this, generation of electricity using sustainable energy resources can be more productive. This paper describes a hybrid Electrical Power Generation model by integrating photovoltaic Solar Energy and Wind Energy without disturbing the ecological balance. Basically we can achieve uninterrupted power by using this hybrid energy system. Moreover this process reduces the generation cost to a minimum value. The equipment consists of combination of PV solar-cell, a mast mounted wind generator, storage batteries and an inverter used to convert DC power to AC power throughout the system. This hybrid solar-wind power generating system is suitable for both Industries and domestic utilization